Preexisting antigen‐specific immune responses are modulated by oral KLH feeding in humans. Issue 7 (27th April 2015) - Hostmann, Arwed; Meyer, Tim; Maul, Jochen; Preiss, Jan; Boortz, Bertram; Thiel, Andreas; Duchmann, Rainer; Ullrich, Reiner
<x xml:space="preserve">Abstract</x> Oral tolerance is the antigen‐specific inhibition of a systemic immune response after oral antigen uptake and well established in animal models. We recently showed that keyhole limpet hemocyanin (KLH) feeding modulates subsequently induced systemic immune responses in humans as well. In the present study, we investigated whether oral KLH can also modulate preexisting antigen‐specific systemic B‐ and T‐cell responses. We induced delayed‐type hypersensitivity (DTH) reactions as well as systemic KLH‐specific B‐ and T‐cell responses by subcutaneous KLH injections. Subsequent oral KLH administration decreased the small proportion of antigen‐specific CD4+ T cells positive for the cytokine IL‐17 at the end of the feeding regimen even further. After reimmunization, there was no difference in DTH reactions and the KLH‐specific B‐cell responses, but KLH‐fed volunteers had an increased proportion of antigen‐specific CD4+ T cells positive for IL‐10 and a reduced proportion of antigen‐specific CD4+ T cells positive for the skin‐homing receptor cutaneous lymphocyte antigen and IL‐2 and IFN‐γ. Taken together, oral KLH can modulate a preexisting systemic KLH‐specific immune response. These results suggest that feeding antigen may offer therapeutic strategies for the suppression of unwanted immune reactions in humans.